The authenticity of women who decided for a natural childbirth: experiences - Elayne Arantes Elias; Dayanne Teresinha Granetto Cardoso Floriani; Letycia Sardinha Peixoto Manhães; Andyara do Carmo Pinto Coelho Paiva; Fabrício Bruno Cardoso; Lauanna Malafaia da Silva; Nelson Augusto Mendes (Universidade Federal do Ceará, 2022)
Objective: to understand the meanings of experiences of women who have undergone natural childbirth. Methods: heideggerian qualitative phenomenological research with 14 women carried out through open audiorecorded interviews, transcribed and analyzed whose steps were the routing for constitution of units of meaning, understanding and hermeneutics. Results: most of them decided to give birth normally and this experience meant: having chosen and dreamed of natural birth because it was better, having planned to give birth, having known how the moment would be and that it was a great experience allied to the feeling of being more powerful and strong and that they would advise other women without any regrets. Despite the positive experience, many did not receive information about childbirth. Conclusion: the experience of natural birth proved to be authentic due to the women's decision, with assertive reports, which is provided by quality assistance by obstetric nursing, active from prenatal to postpartum. Contributions to practice: reflection and strengthening of the obstetric nurse's actions in this process, which goes from prenatal care to labor, childbirth, and puerperium, following the guidelines of good practice in women's health care and public health policies.